PERTANGGUNGJAWABAN PIDANA TURUT SERTA MELAKUKAN KEKERASAN TERHADAP ANAK YANG MENGAKIBATKAN LUKA BERAT: (ANALISIS PUTUSAN NOMOR 181/PID.SUS/2023/PN SGN.) - Shurohudin, Imam; Kuncoro, Cipto; Serbabagus, Shalahudin (LAW Specialist Jurnal Ilmiah Hukum, 2024)
Children are a gift and a mandate from God Almighty, in whom inherent dignity and honor as a whole human being. Cases of violence against are increasingly massive and complex, then Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection was issued to protect children’s rights specifically. This study uses a normative legal method with a focus on analyzing the basis for the Sragen District Court Judge’s Decision Number 181/Pid.Sus/2023/PN Sgn. Normatively, the regulations related to criminal acts involving children according to the Child Protection Law are more comprehensive, further regulating special protection and rehabilitation for children, while the Criminal Code only focuses on criminal sanctions. The Panel of Judges examining the case has conducted the qualification, constitutive, and constitutive stages of finding facts in the form of statements from witnesses, victim witnesses, and investigator witnesses, statements from the defendant, written evidence in the form of visum et repertum results, birth certificate extracts, and several pieces of evidence so that they can impose criminal sanctions of imprisonment and restitution payments by the Convicts.